Analisis Wacana Kritis Pada Berita Kriminal Surat Kabar Posmetro Padang - Silvia Permata Sari (Majalah Ilmiah UPI YPTK, 2018)
Understanding of the hidden intent or meaning behind the news texts can be known through critical discourse analysis. The basic understanding of critical discourse analysis is that discourse is not understood merely as an object of study of language but language as a tool used for certain purposes and practices including ideological and power practices. The data of this research are news texts with criminal problems in the newspaper Posmetro Padang. The source of this research data is the daily news of Posmetro Padang. Theo van Leeuwen's critical discourse analysis model is one of six critical discourse analysis models that allow the reader to know how a group or someone is marginalized or even favored in a news discourse. In addition, it helps so that readers can think more critically in analyzing a news discourse. Not only read but understand and interpret it so that it can know the hidden purpose in the news text.